Teachers' perspectives on the challenges of teaching mathematics in South Africa - Agyeman, Nana Yaw Brenya; Thami Isaac Makhoba; Nomxolissi Mitsi; Avela Ngqungunza; Lunglwa Nqoma; Shakespear Chiphambo (Universitas Papua, 2025)
This study addresses the persistent challenges encountered by South African teachers in mathematics instruction at the intermediate phase level. It specifically explores teachers' perceptions of the factors that hinder effective mathematics teaching in intermediate-phase schools within the Chris Hani District. The primary objective of the study was to examine teachers’ perspectives and the contextual conditions influencing instructional practices, with the aim of informing targeted interventions. A qualitative research approach was employed, utilizing a phenomenological design to explore the lived experiences of the participants within their cultural and social contexts. Purposive sampling was used to select eight participants with substantial experience in teaching at the intermediate phase level. Data were collected through semi-structured interviews, which provided a balance between flexibility and depth, allowing for the exploration of participants’ insights. Thematic analysis was conducted to identify recurring themes and patterns within the data. One of the key findings was that teachers struggled to meet the individual learning needs of students. Participants also expressed concerns about the unrealistic demands of the curriculum and emphasized the urgent need for curriculum reform. These challenges highlight the necessity of implementing strategies to enhance the quality of mathematics teaching. The study recommends increased investment in professional development programs focused on mathematics education and calls for curriculum reform initiatives led by educational authorities to address teachers’ concerns, particularly regarding workload. In addition to improving instructional practices, these reforms should address broader systemic issues that impede effective mathematics instruction. Overall, this study contributes to the growing body of knowledge on the challenges facing mathematics education in South Africa and underscores the need for contextually responsive policy interventions.